PENGARUH KUALITAS PRODUK, HARGA DAN PELAYANAN TERHADAP KEPUTUSAN KONSUMEN MEMBELI PRODUK - Hapsari, Leona Febi; Maruf, Adam; Setiawan, Chandra; Sanjaya, Vicky F (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2020)
Competition is getting tougher with the circulation of minimarkets throughout the city, requiring business people to maximize their performance through product quality, price and service quality in order to survive in business competition and be able to create consumer decisions to buy products. This study aims to examine the effect of product quality, price, and service on product buying decisions. The method used in this study was a cross-sectional survey design. The sample in this study we took from 100 respondents who live in the BandarLampung area. The statistical test was carried out using SmartPLS-based Structural Equation Modeling. The validity test uses factor loading, while the reliability test uses the cronbach'c alpha value, composite reliability and Average Variance Extracted (AVE). After the results of the indicators used are valid and reliable, then the hypothesis is tested. Of the three proposed hypotheses, all are supported. The conclusion of this research is the importance of maintaining product quality, price, and service properly and effectively so that consumer decisions to buy products are high